Tratamento da migranea refratária na unidade de emergência do complexo hospitalar de barbacena – rede FHEMIG - Cunha, Sara Luiza Ronzani da; Jurno, Mauro Eduardo; Andrade, Priscilla Garcia de (Headache Medicine, 2024)
Headache is one of the primary neurological complaints in emergency departments. It is not uncommon for headaches to persist even with appropriate treatment. The initial evaluation should differentiate between primary and secondary headaches, determine the need for further investigation, and treat the acute pain. Migraines, in particular, are among the most disabling primary headches, affecting quality of life and burdening the healthcare system. Refractory migraine is characterized by the lack of response to standard preventive and acute treatment, requiring a more aggressive therapeutic approach. The objective of the study is to evaluate the therapeutic response in the treatment of refractory migraine at the Emergency Department of the Barbacena Hospital Complex, two hours after the administration of a combination of 5 mg of intravenous or oral haloperidol and intravenous or oral dexamethasone in patients classified as refractory to initial treatment. The study was conducted as a prospective observational study with patients considered refractory to initial migraine treatment. Patients who did not respond to at least three adequate dose medications were included. After obtaining consent, demographic data and medical histories were collected, and patients completed the Visual Analog Scale (VAS) to quantify pain. They received 5 mg of haloperidol (oral or intravenous) and 4 mg of dexamethasone (oral or intravenous). After two hours, pain intensity was reassessed and quantified. The study is ongoing, with data collection from August 1, 2023, to July 31, 2024. However, with the end approaching, it is now possible to evaluate the results and clarify the proposed objective. Currently, there are 16 patients, 15 females and 1 male, with an average age of 28 years. The results are favorable, showing improvement after therapy by at least 2 points on the VAS and a maximum of 10 points, with only one result indifferent to the treatment. The combination of haloperidol and dexamethasone appears promising in treating patients who do not respond to conventional therapy, providing significant pain relief. This approach can reduce patient morbidity and healthcare costs. Additional studies are needed to optimize the doses and combinations of these medications to maximize efficacy and minimize risks.